2004
DOI: 10.1126/science.1092185
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Polymers as Major Components of Atmospheric Organic Aerosols

Abstract: Results from photooxidation of aromatic compounds in a reaction chamber show that a substantial fraction of the organic aerosol mass is composed of polymers. This polymerization results from reactions of carbonyls and their hydrates. After aging for more than 20 hours, about 50% of the particle mass consists of polymers with a molecular mass up to 1000 daltons. This results in a lower volatility of this secondary organic aerosol and a higher aerosol yield than a model using vapor pressures of individual organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
1,045
6
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,024 publications
(1,147 citation statements)
references
References 27 publications
68
1,045
6
6
Order By: Relevance
“…35 As a result, in addition to van der Waals interactions, it should ideally form hydrogen bonds with solutes which undergo such a type of interaction, particularly via the surface chains. Secondary organic aerosol (SOA) polymers originated from oxidation of aromatic species could potentially undergo similar interactions, based on the molecular structures proposed by Kalberer et al 34 Holmgren et al 48 proposed several polymer− air ppLFER models including those for cellulose-based materials and polyurethane. A urethane unit has a number of sites which could participate in H-bonding; therefore, one could expect polyurethane to simulate molecular interactions similar to those anticipated for cellulose and SOA polymers.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…35 As a result, in addition to van der Waals interactions, it should ideally form hydrogen bonds with solutes which undergo such a type of interaction, particularly via the surface chains. Secondary organic aerosol (SOA) polymers originated from oxidation of aromatic species could potentially undergo similar interactions, based on the molecular structures proposed by Kalberer et al 34 Holmgren et al 48 proposed several polymer− air ppLFER models including those for cellulose-based materials and polyurethane. A urethane unit has a number of sites which could participate in H-bonding; therefore, one could expect polyurethane to simulate molecular interactions similar to those anticipated for cellulose and SOA polymers.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Aromatic peroxy radicals (RO 2 ) react with HO 2 under low NO x conditions to form non-volatile SOA while they reacted with NO under high NO x conditions to form semi-volatile SOA. In addition, the Base model treats the acid enhancement of isoprene SOA (Surratt et al, 2007) and irreversible particle-phase oligomerization (Kalberer et al, 2004), which converts semi-volatile condensed-phase species into non-volatile species. We do not consider SOA formation from IVOCs or via aqueous-phase processing.…”
Section: Base Soa Modelmentioning
confidence: 99%
“…The UCD/CIT air quality model is a regional chemical transport model (CTM) (Kleeman and Cass, 2001) that has been extensively used for predicting regional aerosol concentrations, including SOA (Chen et al, 2010;Kleeman et al, 2007). The UCD/CIT model simulates the emissions, transport, gas-phase chemistry, aerosol physics and chemistry (dynamic gas/particle partitioning, coagulation, thermodynamics and deposition) in the lower troposphere.…”
Section: -D Air Quality Modelmentioning
confidence: 99%
“…Such difficulties likely arise from complexity in the sources (including both primary combustion emissions, POA, and secondary production SOA), composition, and chemistry of OA. While traditionally SOA has been thought to consist of products from a few classes of compounds (terpenes and aromatics), recent studies have identified both additional precursors [Kroll et al, 2005;Lim and Ziemann, 2009;Robinson et al, 2007;Volkamer et al, 2009] and additional formation pathways [Carlton et al, 2007;Kalberer et al, 2004]. Once formed in the atmosphere, the pool of OA remains dynamic, through both reversible partitioning and continued atmospheric oxidation.…”
Section: Introductionmentioning
confidence: 99%